Die ontwikkeling van die leerstelling van Goddelike genesing in die Apostoliese Geloof Sending van Suid-Afrika: Enkele kerkhistoriese perspektiewe - Nel, Marius (Verbum et ecclesia, 1993)
The development of the doctrine of divine healing in the Apostolic Faith Mission of South Africa: some church historical perspectives In this study attention is given to the development of the doctrine of divine healing in the A.F.M of S.A., starting with its historical roots found in the holiness and revivalistic movements of the nineteenth century. A description of the preaching of the doctrine in the A.F.M of S.A. through the eighty five years of its history follows.